Contrariwise obesity through organic food consumption in Malaysia: a signaling theory perspective - Abdullah, Zulhamri; Putri, K. Y. S.; Raza, Syed Hassan; Istiyanto, S. Bekti (BioMed Central Limited., 2022)
Background: the context and purpose of the study Unhealthy food consumption has raised an alarming situation of obesity among Asian nations and posing serious threats to human health. Recent studies have acknowledged that organic food consumption has been contrariwise associated with obesity. The consumption of healthy food has received research attention in social marketing and several antecedents and consequences have been identified. However, to date, there is a void in literature that how social, individual, and marketing elements together tradeoff in predicting a healthy lifestyle. Thus, the current investigation unfolds the antecedents of healthy foods’ adoption in Asia by integrating the brand signaling and theory of planned behavior.